Ion Chemistry in Dielectric Barrier Discharge Ionization: Recent Advances in Direct Gas Phase Analyses - Dryahina, Kseniya; Polášek, Miroslav; Jašík, Juraj; Sovová, Kristýna; Španěl, Patrik (Mass spectrometry reviews, 2024)
Dielectric barrier discharge ionization (DBDI) sources, employing low-temperature plasma, have emerged as sensitive and efficient ionization tools with various atmospheric pressure ionization processes. In this review, we summarize a historical overview of the development of DBDI, highlighting key principles of gas-phase ion chemistry and the mechanisms underlying the ionization processes within the DBDI source. These processes start with the formation of reagent ions or metastable atoms from the discharge gas, which depends on the nature of the gas (helium, nitrogen, air) and on the presence of water vapor or other compounds or dopants. The processes of ionizing the analyte molecules are summarized, including Penning ionization, electron transfer, proton transfer and ligand switching from secondary hydrated hydronium ions. Presently, the DBDI-MS methods face a challenge in the accurate quantification of gaseous analytes, limiting its broader application in biological, environmental, and medical realms where relative quantification using standards is inherently complex for gaseous matrices. Finally, we propose future avenues of research to enhance the analytical capabilities of DBDI-MS.
Keywords: gas phase; ion chemistry; direct analyses; dielectric barrier discharge ionization